Preparation and characterization of long-term stable pullulan nanofibers via in situ cross-linking electrospinning - Zongjie Li; Tiandi Pan; Yuke Wu; Weimin Kang; Yong Liu (Adsorption Science & Technology)
Pullulan nanofibers with long-term stabilization were fabricated by using glutaraldehyde as the cross-linking agent and sulfuric acid as the catalyzer via in situ cross-linking electrospinning. The structural, chemical, and thermal analyses have been conducted by field emission scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and differential scanning calorimetry. Cross-linked pullulan nanofibers were found thermally more stable. More importantly, the water absorption and water solubility of the cross-linked pullulan nanofiber membranes were evaluated. The results showed that the water absorption rate increased significantly (from 327% to 651%) and the weight loss rate decreased (from 19.0% to 4.1%) with the increase of glutaraldehyde content. Overall, this in situ cross-linking electrospinning technique provides a method to cross-link pullulan during electrospinning. The cross-linked pullulan nanofibers could be employed as promising materials for a variety of potential applications in adsorption and separation fields.